Evaluation of micro RNA expression profiles during BCG infection in the presence and absence of endogenous and synthetic steroids and possible implications on the host immune response to the pathogen - Thiart, Leani (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScMedSc)--Stellenbosch University, 2014.